2006
DOI: 10.1007/s11224-006-9111-4
|View full text |Cite
|
Sign up to set email alerts
|

The structure and thermochemistry of 3:4,5:6-dibenzo-2-hydroxymethylene-cyclohepta-3,5-dienenone (1) and some related compounds

Abstract: Condensed and gas phase enthalpies of formation of 3:4,5:6-dibenzo-2-hydroxymethylene-cyclohepta-3,5-dienenone (1, f H • m ( − 199.1 ± 16.4), ( − 70.5 ± 20.5) kJ mol −1 , respectively) and 3,4,6,7-dibenzobicyclo[3.2.1] nona-3,6-dien-2-one (2, ( − 79.7 ± 22.9), (20.1 ± 23.1) kJ mol −1 ) are reported. Sublimation enthalpies at T = 298.15 K for these compounds were evaluated by combining the fusion enthalpies at T = 298.15 K (1, (12.5 ± 1.8); 2, (5.3 ± 1.7) kJ mol −1 ) adjusted from DSC measurements at the meltin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…However, as discussed in Section 3.1, the reason for this discrepancy lies in the few incorrect pressures that Kahlbaum measured at the lower and upper temperatures. It should also be noted that the enthalpies of vaporisation derived for this compound by correlation with gas chromatography [29][30][31] are systematically somewhat higher than those determined by conventional methods. The reason for this discrepancy is that the correlations made in these papers are based on the data set of alkyl parabens by Perlovich et al 33 However, as shown in our earlier work, 22 this data set is in conflict with other data available for alkyl parabens.…”
Section: Pccp Papermentioning
confidence: 80%
“…However, as discussed in Section 3.1, the reason for this discrepancy lies in the few incorrect pressures that Kahlbaum measured at the lower and upper temperatures. It should also be noted that the enthalpies of vaporisation derived for this compound by correlation with gas chromatography [29][30][31] are systematically somewhat higher than those determined by conventional methods. The reason for this discrepancy is that the correlations made in these papers are based on the data set of alkyl parabens by Perlovich et al 33 However, as shown in our earlier work, 22 this data set is in conflict with other data available for alkyl parabens.…”
Section: Pccp Papermentioning
confidence: 80%
“…An especially extended amount of research has been done with hydrocarbons including alkanes, alkenes, alkynes, and aromatics , forming the core of the various carbon groups. In addition, many data have dealt specifically with alcohols and phenol derivatives [61][62][63][64][65][66][67][68][69][70][71][72][73][74], ethers [75][76][77][78][79][80][81][82][83][84], carbaldehydes [85][86][87][88][89][90][91][92][93][94], ketones [95][96][97][98][99][100][101][102][103][104][105][106][107][108][109]...…”
Section: Sources Of Heat-of-combustion and Formation Datamentioning
confidence: 99%
“…The next paper by Perişanu et al [357] is a continuation of the work on thermochemical properties of dibenzocycloalkane derivatives [358] and deals with the structure and thermochemistry of 3:4,5:6-dibenzo-2-hydroxymethylene-cyclohepta-3,5-dienenone and 3,4,6,7-dibenzobicyclo[3.2.1]nona-3,6-dien-2-one. Condensed and gas phase enthalpies of formation are reported as well as the finding that the former compound exists entirely in the enol form.…”
Section: Issuementioning
confidence: 99%